Integrating Maqaṣid al-Shariah into the Sustainable Development Goals: A Comparative Analysis from an Islamic Economic Perspective - Wulandari, Nurul; Aziz, Abdul; Wartoyo (Jeksyah: Islamic Economics Journal, 2025)
This study explores how Maqasid al-Shariah provides a robust foundation for developing a sustainable and inclusive economic system aimed at achieving human welfare and happiness through fair and balanced wealth distribution at both individual and societal levels. It discusses how the principles of Maqasid al-Shariah can guide the formulation of economic policies that prioritize collective well-being and environmental sustainability. The research adopts a qualitative approach using a literature-based study, examining relevant theories and scholarly works within the framework of Maqasid al-Shariah and Islamic economics. The findings reveal that Islamic economics has evolved as a viable alternative to the conventional global economic system because it is rooted in divine values, justice, equitable wealth distribution, the prohibition of usury (riba) and uncertainty (gharar), as well as a strong sense of social responsibility. These principles closely align with the objectives of the Sustainable Development Goals (SDGs), promoting prosperity in both this world and the hereafter while ensuring environmental and social sustainability. Anchored in Maqāṣid al-Sharī‘ah, Islamic economics emphasizes fulfilling essential needs and generating collective benefit (maslahah), rather than pursuing mere material gain. This ethical orientation positions Islamic economics as a more just, equitable, and sustainable alternative to conventional systems. Furthermore, ijtihad-based approaches grounded in public benefit are crucial to keeping Islamic economics relevant to contemporary challenges while preserving the spirit of Sharia in all economic activities.